Application of Three-Dimensional (3D) Printing in Neurosurgery - Hao Li; Linyun Lu; Ning Li; Liu Zi; Qian Wen (Advances in Materials Science and Engineering)
Three-dimensional (3D) printing has been increasingly used in various fields of medicine, such as in auxiliary diagnosis and treatment, medical teaching, and regenerative medicine. Most operations performed by neurosurgeons and associated pathological examinations involve complex, microscopic anatomical structures that cannot be observed outside. 3D-printed models can reproduce anatomical structures, pathological tissues, and cells with high accuracy, enhancing our understanding of complex aspects of anatomy and pathology. They can also assist in preoperative planning and simulation, help in surgical or interventional surgery precision medicine, and improve the effectiveness of treatments. This review comprehensively summarizes and discusses its current application progress and problems, including treatments for common diseases (e.g., intracranial tumors, intracranial hemorrhage, intracranial aneurysms, skull repair, and neural prosthetics), clinical training, and preoperative plans. With its widespread applications, 3D printing as an innovative tool will provide new directions for developing imaging, strategies, and interventions in neurosurgical diseases.